Cities, Change & Conflict - Kleniewski, Nancy (Thomson Wadsworth, 2006)
CITIES, CHANGE, AND CONFLICT - A POLITICAL ECONOMY OF URBAN LIFE discusses the importance of cities for the economic, cultural, and political life of modern societies. The authors consistently use the political economy perspective to introduce students to the basic concepts and research in urban sociology, while also acknowledging the contributions of the human ecology perspective. Through the use of case studies, the presentation remains accessible and down-to-earth, engaging the student in the material.